ANALISIS KELAYAKAN PENGEMBANGAN USAHA NATA DE COCO PADA CV AMARTA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR: Feasibility Analysis of Nata De Coco Business Development on CV Amarta Kempas Subdistrict Indragiri Hilir District - Putri Wahyuni; Fajar Restuhadi; Vonny Setaries Johan (Universitas Darussalam Gontor, 2022)
Nata de coco is a food product made from coconut water. Nata de coco processing business has the potential to be developed because it can utilize coconut processing by-products. CV Amarta is one of the industries where coconut flesh is processed into copra and coconut water as a secondary yield. CV Amarta will develop a coconut business by establishing a nata de coco processing business. Setting nata de coco business needs to do a feasibility analysis of business development as a consideration in making decisions regarding the possibility of the success of a business idea. This research aims to analyze the feasibility of developing a nata de coco business at CV Amarta in terms of financial and non-financial aspects so that it can be declared feasible or infeasible. The research methods are to analyze the non-financial aspects of the market, technical, management, legal, and environmental described as descriptive and analyzed financial aspects based on investment criteria such as BEP, NPV, IRR, B/C ratio, payback period, and sensitivity analysis. The nata de coco business development at CV Amarta is feasible in terms of non-financial and financial aspects with the results of BEP 528.176 units, BEP acquisition of Rp 1.056.352.623, the value of NPV is Rp 166.216.342, IRR 16%, payback period 4,7 years, and B/C ratio 1,10. The sensitivity analysis shows this business development is sensitive, with a 5% decrease in selling price and a 5% increase in variable cost.